Revision of the type species of Syllepte Hübner and other spilomeline genera recently synonymized (Lepidoptera: Crambidae) - Solis, M. Alma; Mally, Richard; Hayden, James E.; Nuss, Matthias (Zootaxa, 2023)
The identity of Syllepte Hübner, 1819–21 is revised by designating a neotype from Neomabra Dognin, 1905, rev. syn., for the type species S. incomptalis Hübner, 1819–21 because the original type material is lost, and we consider it to be congeneric with Syllepte. We redescribe Syllepte based on S. incomptalis and S. nitidalis (Dognin, 1905), rev. comb., and place Syllepte in Agroterini Acloque, 1897, and consequently synonymize Syleptinae [sic] Swinhoe, 1900, syn. rev., with Agroterini. Pantographa Lederer, 1863 and Micromartinia Amsel, 1957 are redescribed, diagnosed, and restored to their status as valid genera, rev. stat., also in the tribe Agroterini. We designate lectotypes for Neomabra nitidalis Dognin, 1905, new lectotype, rev. comb., and Pantographa scripturalis (Guenée, 1854), new lectotype, rev. stat., to stabilize the names of these species. Pantographa is compared to Haritalodes Warren, 1890. We newly combine Pantographa gorgonalis Druce, 1895, n. comb., rev. stat., and Pilocrocis cyrisalis (Druce, 1895), n. comb., with Micromartinia. One hundred and ninety-six species are listed that remain misplaced in the polyphyletic Syllepte and need further revision to determine their identity and proper generic placement.